The Story of Women in Colonial India: Their Socio- Political Roles in the 18th and 19th Centuries: Women's Empowerment and Political Mobilization in Colonial India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The paper aims to illustrate the status of women in a situation in which even the best of male attempts were inadequate and their initiatives to lift themselves from a place of disrepute and neglect where society had denied them. The women's position was not only ignored but also underplayed between 1750 and 1900, when the imperial rule in India was at its height and sparks of agitation against colonial control began to moulder. Women like Rani Laxmibai, Rama Pandita Bai, Savitribai Phule, Tarabai Shinde, Anandibai Joshi and Sarojini Naidu may be influential participants in a male controlled socio-political discourse. The popularity of certain well-known personalities, though, reflects a bad judgement showing the degree to which even the average women have transcended the challenges to elevating themselves from the downtrodden situation in which posterity has drifted them.In the 19th century, the anvil of the socio-religious reform revolution came into being. Women's unique concerns shaped the foundation of these campaigns, which represent the onset of a modern era of awareness that began to infiltrate the community as a whole. Efforts to change in this era also culminated not only in immediate outcomes in changing the status of women both economically and constitutionally, but also in creating further opportunities for greater role for women in defining the anti-colonial stance of the 19th century. The phenomenon of the 19th century opened up the 20th century to a whole new environment for women, which eventually allowed the movement of Gandhi women in nationalist struggle. A brief narrative of the life stories of iconic women thus helps demonstrate that they have adapted to the existing world and opened up more opportunities in the 20th century for women's political mobilization.